APOBEC3A, APOBEC3B, and APOBEC3H Haplotype 2 Restrict Human T-Lymphotropic Virus Type 1 - Ooms, Marcel; Krikoni, Aikaterini; Kreß, Andrea; Simon, Viviana; Muenk, Carsten (Journal of Virology, 2012)
The human APOBEC3 family consists of seven cytidine deaminases (A3A to A3H), some of which display potent antiretroviral activity against HIV-1 and other retroviruses. Studies that analyzed the effect of A3G on human T-lymphotropic virus type 1 (HTLV-1) infectivity resulted in conflicting findings, and our knowledge of HTLV-1 restriction by other A3 proteins remains limited. Since HTLV-1, much like HIV, targets CD4+ T cells, we hypothesized that A3 proteins other than A3G restrict HTLV-1. All seven human A3 proteins were tested in HTLV-1 reporter and HIV-1 infectivity assays. We show that A3A, A3B, and A3H haplotype 2 (A3H hapII) acted as potent inhibitors of HTLV-1. Wild-type HIV-1, in contrast, was restricted by A3B and A3H hapII, but not by A3A. Catalytic site mutants of A3A, A3B, and A3H hapII showed that A3A and A3B restriction of HTLV-1 required deaminase activity. However, A3H hapII acted in a deaminase-independent manner when restricting HTLV-1, while requiring deaminase activity for HIV-1 restriction. We also analyzed A3 editing of HTLV-1 in five T-cell lines obtained from HTLV-1-infected patients. These cell lines contained extensively edited HTLV-1 sequences with G-to-A mutations in dinucleotide contexts suggestive of APOBEC3 mutagenesis. Comparison of the A3-induced mutations from reporter cells and the patient-derived cell lines indicate that A3G but also other A3 members, possibly A3A and A3B, affect HTLV-1 in vivo. Taken together, our data indicate that HTLV-1 is a likely target for multiple A3 proteins. © 2012, American Society for Microbiology.
Created from Fastlane, Scopus look-up